2022
DOI: 10.3390/d14060478
|View full text |Cite
|
Sign up to set email alerts
|

Root-Associated Endophytic and Mycorrhizal Fungi from the Epiphytic Orchid Maxillaria acuminata in a Tropical Montane Forest in Southern Ecuador

Abstract: In natural environments, it has been shown that orchids interact with multiple microorganisms including various species of fungi that colonize their tissues. The diversity of these fungi associated with orchid roots is still being described along with the ecological role they play when interacting with the orchids. In this study, we evaluated the richness and diversity of the endophytic and mycorrhizal fungi associated with the roots of Maxillaria acuminata, a common epiphytic orchid species from a tropical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…As reported in parasitic plants, the microbial transfer might also occur between the epiphytic plants and their host. Studies in epiphytic orchids reported that the root fungal composition of epiphytic orchids is dominated by Ascomycota and Basidiomycota (Cevallos et al 2018;Maldonado et al 2020;Cevallos et al 2022), while the bacterial composition in the root is dominated by Cyanobacteria (Tsavkelova et al 2001;Tsavkelova et al 2003a;Tsavkelova et al 2003b;Tsavkelova et al 2022). However, whether the microbial community in the root of epiphytic orchids originated from the host plants is unknown since there is still no study on microbial correlation and interaction between epiphytic plants and their host currently Very few studies have investigated the microbial composition in vascular epiphytic and parasitic plants and their respective host.…”
mentioning
confidence: 99%
“…As reported in parasitic plants, the microbial transfer might also occur between the epiphytic plants and their host. Studies in epiphytic orchids reported that the root fungal composition of epiphytic orchids is dominated by Ascomycota and Basidiomycota (Cevallos et al 2018;Maldonado et al 2020;Cevallos et al 2022), while the bacterial composition in the root is dominated by Cyanobacteria (Tsavkelova et al 2001;Tsavkelova et al 2003a;Tsavkelova et al 2003b;Tsavkelova et al 2022). However, whether the microbial community in the root of epiphytic orchids originated from the host plants is unknown since there is still no study on microbial correlation and interaction between epiphytic plants and their host currently Very few studies have investigated the microbial composition in vascular epiphytic and parasitic plants and their respective host.…”
mentioning
confidence: 99%